Suboptimal management of hypernatraemia in acute medical admissions. (26th March 2021) - Brennan, Michelle; Mulkerrin, Lorcan; Wall, Deirdre; O'Shea, Paula M; Mulkerrin, Eamon C
Abstract: Background: Hypernatraemia arises commonly in acute general medical admissions. Affected patients have a guarded prognosis with high rates of morbidity and mortality. Age-related physiology and physical/cognitive barriers to accessing water predispose older patients to developing hypernatraemia. This study sought to perform a descriptive retrospective review of hypernatraemic patients admitted under acute general medicine teams. Methods: A retrospective cross-sectional study of a sample of acute medical in-patients with serum[sodium]>145 mmol/L was conducted. Patients were exclusively older(>69 years) and admitted from Nursing homes (NH)(41%) and non-NH pathways(59%). A comparison of management of NH /non-NH patients including clinical presentation, comorbidities, laboratory values, [sodium] monitoring, intravenous fluid regimes and patient outcomes was performed. Results: In total, 102 consecutive patients (males, n=69(67.6%)) were included. Dementia and reduced mobility were more common in NH residents and admission serum [Sodium] higher (148 vs 142 mmol/L/p=0.003). Monitoring was inadequate: no routine bloods within the first 12h in >80% of patients in both groups. No patient had calculated free water deficit documented. More NH patients received correct fluid management (60% vs 33%/p%0.015). Incorrect fluid regimes occurred in both groups (38% vs 58%/p=0.070). Length of stay in discharged patients was lower in NH, (8(4‐20) vs 20.5(9.8‐49.3 days)/p=0.003). Time to death for NH residents was shorter (9(5.5‐11.5) vs 16 (10.25‐23.5) days/p=0.011). Conclusion: This study highlights suboptimal management of hypernatraemia. Implementation of hypernatraemia guidelines for general medical older inpatients are clearly required with mechanisms to confirm adherence. Health care workers require further education on diagnostic challenges of dehydration in older people and the importance of maintaining adequate hydration.